Case Report: Adrenal gland splenosis mimicking a neuroendocrine tumor on 68Ga-DOTATATE and 18F-FDG PET/CT imaging - Hu, Xianwen; Zhao, Wei; Wang, Pan (Frontiers in Medicine, 2025)
Splenosis occurring in adrenal glands is relatively rare and is easily misdiagnosed as neoplastic lesions. Herein, we present a case of a 39-year-old woman who underwent a pancreatic tail resection and splenectomy 8 years ago due to caudal pancreatic neuroendocrine tumor and splenic invasion. She underwent abdominal ultrasound examination in an external hospital a month ago due to abdominal discomfort and found a lump in the left adrenal gland. She was admitted to our hospital for further diagnosis and treatment. Abdominal computed tomography (CT) examination revealed a nodule of equal soft tissue density on her left adrenal gland, which presented obvious uniform enhancement on contra-enhanced CT. Subsequently, she underwent fluorine-18 fluorodeoxyglucose (18F-FDG) and gallium-68 labeld 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraaceticacid -D-Phel-Tyr3-Thr8-OC (68Ga-DOTATATE) positron emission tomography (PET)/CT imagings, and showed slightly increased 18F-FDG uptake and obviously increased 68Ga-DOTATATE uptake in the lesion, suggesting the possibility of neuroendocrine tumor metastasis. However, postoperative pathology confirmed that the lesion was splenosis. Our case suggests that adrenal gland splenosis should be considered as a differential diagnosis of adrenal tumors, understanding the clinical and imaging features of splenosis can reduce misdiagnosis and avoid unnecessary surgical intervention.